The crime of breach of trust - Djillali Ben Tayeb Djillali (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The crime of breach of trust is among the crimes against funds, which directly targets the transaction that occurs between the victim and the offender, as this crime is meant to be the violation of a person's right to the property of another person by breach of trust deposited in him, so that delivery must take place as a temporary possession based on a contract of trust, which is approved by the Algerian legislator original and complementary penalties, and this is due to the special nature of such transactions that fall on it This kind of crime.